Analisis Tingkat Efektivitas Pemungutan Pajak Bumi dan Bangunan, Pajak Daerah dan Retribusi Daerah dalam Meningkatkan Pendapatan Daerah - Destri Debora Lumbantoruan; Sunarto Wage (Peneliti.net, 2023)
This study aims to analyze the level of effectiveness of collecting land and building taxes, local taxes and regional levies in increasing regional income. The research method used for this research is quantitative with a time series analysis model. Which uses data in the form of secondary reports on the budget analysis of the Batam Regional Revenue Agency (BAPENDA) for the 2017-2021 period. This study shows the results that land and building taxes are partially has a significant and positive effect on local revenue (t count 22.992 > 1.6725 t table), hotel taxes has a significant effect on local revenue (t count 16.904 > 1.6725 t table). Meanwhile, parking fees have a negative value of -7.296 <0.16725, while parking fees do not have a positive effect on local revenue. Simultaneously building and land taxes, hotel taxes and user charges have an effect on local revenue with an F count of 234.500 > 2.77 F table.